3D printing bracket for culturing bone marrow mesenchymal stem cells and application of 3D printing bracket

Prepare zinc and magnesium alloy brackets through 3D printing technology, and form fluoride coating and fiber covers on its surface, solving the problem of biological inertia of existing zinc and magnesium alloy brackets, significantly enhanced its biocompatibility and biological activity, promoted to promote The growth and bone repair effect of osteogeneous stem cells.

CN119367592AInactive Publication Date: 2025-01-28何金杰
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411394491.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The surface of existing zinc-magnesium alloy scaffolds is bioinergenic, which cannot fully induce or stimulate cell behavior, resulting in poor adhesion and growth of bone cells, affecting the bone repair effect.

Method used

The zinc -magnesium alloy bracket is prepared through 3D printing technology, and fluoride coating and fiber covering are formed on its surface to improve biocompatibility and biological activity.

Benefits of technology

It significantly improves the biocompatibility and biological activity of zinc and magnesium alloy stents, promotes the adhesion and growth of concentrated stem cells between bone marrow, and enhances corrosion resistance, anti -inflammatory and antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367592A_ABST
    Figure CN119367592A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a 3D printing stent for bone marrow mesenchymal stem cell culture and application of the 3D printing stent, a zinc-magnesium alloy is used as a base material for laser 3D printing, and then fluorinated coating and fiber coating treatment are performed, so that the biocompatibility and the biological activity of the 3D printing stent are remarkably improved, and the 3D printing stent is suitable for being used for bone marrow mesenchymal stem cell culture. Adhesion and growth of bone marrow mesenchymal stem cells are promoted; the magnesium metal and the zinc metal have mechanical properties similar to those of natural bones, can release magnesium ions and promote osteogenic reaction after being implanted into a body, can be completely degraded into non-toxic substances to be discharged out of the body, and are proved to be potential bone substitute materials; the corrosion resistance of the stent is enhanced by the fluorinated coating, the service life is prolonged, and certain antibacterial and anti-inflammatory characteristics are endowed; sodium alginate and collagen components in the fiber coating layer are beneficial to simulation of an extracellular matrix environment, and cell differentiation and osteogenic reaction are further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a 3D printed scaffold for culturing bone marrow mesenchymal stem cells and an application thereof. Background Art

[0002] In the field of biomedical engineering, bone marrow mesenchymal stem cells (MSCs) have become a research hotspot in regenerative medicine and tissue engineering due to their self-renewal, multidirectional differentiation potential, and immunomodulation. MSCs can not only differentiate into a variety of cell types, such as osteocytes, chondrocytes, adipocytes, etc., but also participate in tissue repair and regeneration processes in vivo and in vitro, and have great application potential in the treatment of various diseases, such as bone injury, cartilage defects, myocardial infarction, etc.

[0003] Scaffold materials are three-dimensional frameworks for seed cells to attach, grow and differentiate. Through interaction with the body system, they can directly affect the repair process and effect of bone tissue defects. Common scaffold materials include metal alloys, bioceramics, natural polymer materials, artificial polymer materials, bioactive glass, etc. Metal alloys have good mechanical properties and can be used as the first choice for orthopedic support materials. Among them, metal alloys such as magnesium, zinc, titanium and other alloys, among which magnesium and zinc have similar mechanical properties to natural bones. When implanted in the body, they can release magnesium ions and promote osteogenesis. At the same time, they can also be completely degraded into non-toxic substances and excreted from the body. They have been proven to be a potential bone replacement material.

[0004] However, the original zinc-magnesium alloy surface is biologically inert and cannot fully induce or stimulate specific cell behaviors, which is not conducive to the adhesion and growth of bone cells. The lack of osteogenesis, vascularization and anti-inflammatory properties will reduce the ability of new bone tissue to grow, thereby increasing the risk of bone repair failure, and ultimately leading to poor integration with surrounding bone tissue and hindering new bone formation or slow bone integration rate, seriously affecting the success rate of orthopedic implant surgery.

[0005] Therefore, how to provide a new stent material with good mechanical properties and biocompatibility, and with anti-corrosion, anti-inflammatory and antibacterial properties is a problem that technical personnel in this field need to solve urgently. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the above-mentioned technology and provide a 3D printed scaffold for culturing bone marrow mesenchymal stem cells and its application.

[0007] In order to solve the above technical problems, the technical solution provided by the present invention is a method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells, comprising the following steps:

[0008] Step 1) 3D printing substrate preparation:

[0009] Select metal zinc and metal magnesium according to the proportion, put them into a melting furnace to melt them, mix them thoroughly and evenly, and after cooling and forming, obtain a molten alloy;

[0010] The alloy melt is used as a raw material for gas atomization powder making, placed in a high-pressure gas atomization powder making device, heated and melted and the temperature is raised to 600-700°C, and the melt is impacted and melted by a high-pressure airflow of 1-3.5MPa, and the melt is broken into gas atomization particles, and after cooling, the zinc-magnesium alloy powder prepared by gas atomization technology is obtained;

[0011] The obtained zinc-magnesium alloy powder is sieved to obtain a zinc-magnesium alloy powder with a particle size of 5-50 μm;

[0012] Step 2) Bracket printing:

[0013] The obtained zinc-magnesium alloy powder was used as a substrate for 3D printing using metal laser printing technology, and the obtained bracket was polished with sandpaper to remove unmelted powder and impurities;

[0014] Then, ethanol and deionized water are used for ultrasonic cleaning for 10-15 minutes, and then dried to obtain the initial zinc-magnesium alloy stent;

[0015] Step 3) Fluorinated coating:

[0016] The initial zinc-magnesium alloy stent is immersed in a sodium fluoride solution with a mass percentage concentration of 8%-23% to perform a fluorination reaction to form a fluorinated coating; after the fluorination reaction is completed, the surface of the stent is cleaned with deionized water to remove the residual fluorinated liquid and impurities. Then, the stent is dried in a drying oven to ensure that the coating is dry and stable, and a zinc-magnesium alloy stent with a fluorinated coating can be obtained;

[0017] Step 4) Fiber coating:

[0018] Dissolve sodium alginate in distilled water at 30°C, stir, swell and dissolve to form a uniform and transparent sodium alginate solution;

[0019] Dissolve the homemade collagen in a 0.5 mol / L acetic acid aqueous solution, stir, swell, and dissolve at room temperature to form a transparent and uniform collagen solution; add a pH regulator to adjust the pH value of the collagen solution to 6.50-6.70;

[0020] 1-3 parts by volume of sodium alginate solution and 2-3 parts by volume of collagen solution are mixed and vigorously stirred to form a homogeneous system, and the blended spinning solution is filtered under a vacuum condition of 3-35 Pa to remove impurities and degas to a uniform solution;

[0021] The prepared spinning solution is mixed with a water-based adhesive, and is sprayed evenly on the surface of the zinc-magnesium alloy bracket by a special fiber spraying device at a controlled pressure of 5-10Mpa. After natural drying, the target product can be obtained.

[0022] Furthermore, in the zinc-magnesium alloy powder of step 1, the mass percentage of metallic zinc is 84-93%, and the mass percentage of metallic magnesium is 7-16%.

[0023] Furthermore, in step 1, the high-pressure gas flow is nitrogen or argon.

[0024] Furthermore, the fluorination reaction time is 1-1.5h.

[0025] Furthermore, the percentage concentration of the sodium alginate solution in step 4 is controlled at 8%-11%.

[0026] Furthermore, the percentage concentration of the collagen solution in step 4 is controlled at 9-13.5%.

[0027] The second object of the present invention is to provide a 3D printed bracket prepared according to the above method.

[0028] The third object of the present invention is to provide an application of the 3D printed scaffold prepared according to the above method in the culture of bone marrow mesenchymal stem cells.

[0029] The advantages of the present invention compared with the prior art are:

[0030] 1) The zinc-magnesium alloy 3D printed stent of the present invention is treated with fluorine coating and fiber coating, which significantly improves its biocompatibility and bioactivity, and promotes the adhesion and growth of bone marrow mesenchymal stem cells;

[0031] 2) Magnesium and zinc have similar mechanical properties to natural bones. When implanted in the body, they can release magnesium ions and promote osteogenesis. They can also be completely degraded into non-toxic substances and excreted from the body. They have been proven to be a potential bone replacement material.

[0032] 3) The fluorinated coating enhances the corrosion resistance of the stent, prolongs its service life, and imparts certain antibacterial and anti-inflammatory properties;

[0033] 4) The sodium alginate and collagen components in the fiber coating layer help simulate the extracellular matrix environment and further promote cell differentiation and osteogenic response; collagen has excellent biocompatibility and biodegradability, making it widely used in bone tissue engineering scaffold materials, and its degradation products can be absorbed by the body; sodium alginate can provide a good three-dimensional growth environment for cells and maintain a good morphology, and its degradation products have no side effects on the human body;

[0034] 5) The preparation method of the scaffold is simple and low-cost, suitable for large-scale industrial production, and has high application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a scanning electron microscope image of the surface morphology of the 3D printed stent in Example 1 of the present invention;

[0036] Figure 2 This is a live-death staining image of cells after the 3D printed scaffold obtained in Example 1 was co-cultured with rBMSCs for 72 hours. DETAILED DESCRIPTION

[0037] The following is a further detailed description of a 3D printed scaffold for culturing bone marrow mesenchymal stem cells and its application in conjunction with the accompanying drawings and embodiments.

[0038] Example 1

[0039] A method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells comprises the following steps:

[0040] 1) 3D printing substrate preparation

[0041] Metallic zinc (90% by mass) and metallic magnesium (10% by mass) are selected, mixed according to the proportion, put into a furnace, heated to a completely molten state and stirred and mixed thoroughly. After cooling, alloy blocks are obtained, which are then broken into small pieces as raw materials for gas atomization powder making.

[0042] The alloy pieces were placed in a high-pressure gas atomization powder making device, heated to 650°C, and 2MPa nitrogen was used as a high-pressure gas flow to impact the melt to break it into gas atomized particles. After cooling, zinc-magnesium alloy powder with a particle size of 30μm was obtained by sieving.

[0043] 2) Bracket printing

[0044] Metal laser printing technology is used, with the zinc-magnesium alloy powder prepared in step 1 as the base material, and 3D printing is performed according to a preset three-dimensional model to form a bracket with a porous structure.

[0045] The printed bracket was first polished with coarse sandpaper to remove large particles and unmelted powder on the surface, and then polished with fine sandpaper until the surface was smooth. After that, it was ultrasonically cleaned with ethanol and deionized water for 12 minutes in turn, and finally dried until completely dry.

[0046] 3) Fluorinated coating

[0047] The cleaned and dried stent was immersed in a sodium fluoride solution with a mass percentage concentration of 15%, maintained at a temperature of 25°C, and a fluorination reaction was performed for 1 hour. After the reaction, the surface of the stent was thoroughly cleaned with deionized water to remove the residual fluoride solution and impurities, and then placed in a drying oven for drying.

[0048] 4) Fiber coating

[0049] Prepare 8% sodium alginate solution by dissolving an appropriate amount of sodium alginate powder in distilled water at 30°C and stirring until completely dissolved.

[0050] At the same time, collagen was dissolved in a 0.5 mol / L acetic acid aqueous solution, and the pH value was adjusted to 6.6 to obtain a transparent and uniform collagen solution with a concentration of 11%.

[0051] Sodium alginate solution and collagen solution were mixed in a volume ratio of 2:2, and stirred vigorously to form a homogeneous system. After filtering and degassing under vacuum conditions, the mixture was mixed with a water-based adhesive.

[0052] Use a dedicated fiber spraying device to evenly spray the mixed liquid on the surface of the bracket at a pressure of 7MPa, and obtain the final product after natural drying.

[0053] Example 2

[0054] A method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells comprises the following steps:

[0055] 1) 3D printing substrate preparation

[0056] Metallic zinc (85% by mass) and metallic magnesium (15% by mass) are selected, mixed in proportion, put into a furnace, heated to a completely molten state, and stirred and mixed thoroughly. After cooling, alloy blocks are obtained, which are then broken into small pieces as raw materials for gas atomization powder making.

[0057] The alloy pieces were placed in a high-pressure gas atomization powder making device, heated to 650°C, and 3MPa argon gas was used as a high-pressure gas flow to impact the melt to break it into gas atomized particles. After cooling, zinc-magnesium alloy powder with a particle size of 30μm was obtained by sieving.

[0058] 2) Bracket printing

[0059] Metal laser printing technology is used, with the zinc-magnesium alloy powder prepared in step 1 as the base material, and 3D printing is performed according to a preset three-dimensional model to form a bracket with a porous structure.

[0060] The printed bracket was first polished with coarse sandpaper to remove large particles and unmelted powder on the surface, and then polished with fine sandpaper until the surface was smooth. After that, it was ultrasonically cleaned with ethanol and deionized water for 12 minutes in turn, and finally dried until completely dry.

[0061] 3) Fluorinated coating

[0062] The cleaned and dried stent was immersed in a sodium fluoride solution with a mass percentage concentration of 20%, maintained at a temperature of 25°C, and a fluorination reaction was carried out for 1.5 hours. After the reaction, the surface of the stent was thoroughly cleaned with deionized water to remove the residual fluoride solution and impurities, and then placed in a drying oven for drying.

[0063] 4) Fiber coating

[0064] Prepare a 10% sodium alginate solution by dissolving an appropriate amount of sodium alginate powder in distilled water at 30°C and stirring until completely dissolved.

[0065] At the same time, collagen was dissolved in a 0.5 mol / L acetic acid aqueous solution, and the pH value was adjusted to 6.6 to obtain a transparent and uniform collagen solution with a concentration of 12%.

[0066] Sodium alginate solution and collagen solution were mixed in a volume ratio of 2:2, and stirred vigorously to form a homogeneous system. After filtering and degassing under vacuum conditions, the mixture was mixed with a water-based adhesive.

[0067] Use a dedicated fiber spraying device to evenly spray the mixed liquid on the surface of the bracket at a pressure of 7MPa, and obtain the final product after natural drying.

[0068] Example 3

[0069] A method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells comprises the following steps:

[0070] 1) 3D printing substrate preparation

[0071] Metallic zinc (93% by mass) and metallic magnesium (7% by mass) are selected, mixed in proportion, put into a furnace, heated to a completely molten state, and stirred and mixed thoroughly. After cooling, alloy blocks are obtained, which are then broken into small pieces as raw materials for gas atomization powder making.

[0072] The alloy pieces were placed in a high-pressure gas atomization powder making device, heated to 650°C, and 3MPa argon gas was used as a high-pressure gas flow to impact the melt to break it into gas atomized particles. After cooling, zinc-magnesium alloy powder with a particle size of 40μm was obtained by sieving.

[0073] 2) Bracket printing

[0074] Metal laser printing technology is used, with the zinc-magnesium alloy powder prepared in step 1 as the base material, and 3D printing is performed according to a preset three-dimensional model to form a bracket with a porous structure.

[0075] The printed bracket was first polished with coarse sandpaper to remove large particles and unmelted powder on the surface, and then polished with fine sandpaper until the surface was smooth. After that, it was ultrasonically cleaned with ethanol and deionized water for 12 minutes in turn, and finally dried until completely dry.

[0076] 3) Fluorinated coating

[0077] The cleaned and dried stent was immersed in a sodium fluoride solution with a mass percentage concentration of 8%, maintained at a temperature of 25°C, and a fluorination reaction was performed for 1 hour. After the reaction, the surface of the stent was thoroughly cleaned with deionized water to remove the residual fluoride solution and impurities, and then placed in a drying oven for drying.

[0078] 4) Fiber coating

[0079] Prepare a 9% sodium alginate solution by dissolving an appropriate amount of sodium alginate powder in distilled water at 30°C and stirring until completely dissolved.

[0080] At the same time, collagen was dissolved in a 0.5 mol / L acetic acid aqueous solution, and the pH value was adjusted to 6.6 to obtain a transparent and uniform collagen solution with a concentration of 13.5%.

[0081] Sodium alginate solution and collagen solution were mixed in a volume ratio of 1:3, and stirred vigorously to form a homogeneous system. After filtering and degassing under vacuum conditions, the mixture was mixed with a water-based adhesive.

[0082] Use a dedicated fiber spraying device to evenly spray the mixed liquid on the surface of the bracket at a pressure of 7MPa, and obtain the final product after natural drying.

[0083] Comparative Example 1

[0084] A method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells comprises the following steps:

[0085] 1) 3D printing substrate preparation

[0086] Metallic zinc (90% by mass) and metallic magnesium (10% by mass) are selected, mixed according to the proportion, put into a furnace, heated to a completely molten state and stirred and mixed thoroughly. After cooling, alloy blocks are obtained, which are then broken into small pieces as raw materials for gas atomization powder making.

[0087] The alloy pieces were placed in a high-pressure gas atomization powder making device, heated to 650°C, and 2MPa nitrogen was used as a high-pressure gas flow to impact the melt to break it into gas atomized particles. After cooling, zinc-magnesium alloy powder with a particle size of 30μm was obtained by sieving.

[0088] 2) Bracket printing

[0089] Metal laser printing technology is used, with the zinc-magnesium alloy powder prepared in step 1 as the base material, and 3D printing is performed according to a preset three-dimensional model to form a bracket with a porous structure.

[0090] The printed bracket was first polished with coarse sandpaper to remove large particles and unmelted powder on the surface, and then polished with fine sandpaper until the surface was smooth. After that, it was ultrasonically cleaned with ethanol and deionized water for 12 minutes in turn, and finally dried until completely dry to obtain the final product.

[0091] Corrosion resistance test of 3D printed bracket

[0092] The corrosion resistance of the 3D printed brackets obtained in Examples 1-3 and Comparative Example 1 was tested using a salt spray test chamber, wherein the salt spray was a 5% NaCl solution, the temperature was controlled at 35°C, the test time was 24 hours, and the rust appearance time during the experiment and the mass loss due to corrosion after the experiment were observed.

[0093] The 3D printed bracket obtained in Comparative Example 1 rusted within 10 minutes, with a mass loss of 13.5 g; the bracket obtained in Examples 1-3 rusted within 40 minutes, with an average mass loss of 3.41 g. The test results show that the 3D printed bracket obtained in Comparative Example 1 rusted earlier, significantly earlier than the brackets obtained in Examples 1-3, and the mass loss of the bracket obtained in Comparative Example 1 due to corrosion was also significantly greater than that of the brackets obtained in Examples 1-3. The reason for this is that the 3D printed bracket in Comparative Example 1 was not treated with a fluorinated coating, and under the action of biological corrosion, its corrosion resistance was significantly lower than that of the 3D printed skeletons obtained in Examples 1-3.

[0094] Biocompatibility test of 3D printed scaffolds

[0095] Rat bone marrow mesenchymal stem cells were taken and prepared into a suspension, which was then inoculated into the 3D printed scaffolds obtained in Example 1 at a certain concentration and cultured for 72 h using H-DMEM medium containing 8% FBS. The live cells and dead cells were distinguished by fluorescent labeling and metabolic activity using the difference in permeability and reactivity of live cells and dead cells to the dye using fluorescent staining technology.

[0096] Figure 1 is a scanning electron microscope image of the surface morphology of the 3D printed bracket in Example 1. Figure 1 It can be seen that the 3D printed scaffold prepared in Example 1 has a complete structure, uniform pore size and high porosity, which is conducive to cell adhesion, proliferation, migration and differentiation, and the transportation of nutrients and metabolites;

[0097] Figure 2 This is a live-death staining image of cells after the 3D printed scaffold obtained in Example 1 was co-cultured with rBMSCs for 72 hours. Figure 2It can be seen that the 3D printed scaffold obtained in Example 1 has excellent biocompatibility, high cell survival rate and good activity, indicating that the material has no cytotoxicity.

[0098] The present invention and its embodiments are described above, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a 3D printed scaffold for culturing bone marrow mesenchymal stem cells, characterized in that: The following steps are involved: Step 1) 3D printing substrate preparation: Select metal zinc and metal magnesium according to the proportion, put them into a melting furnace to melt them, mix them thoroughly and evenly, and after cooling and forming, obtain a molten alloy; The alloy melt is used as a raw material for gas atomization powder making, placed in a high-pressure gas atomization powder making device, heated and melted and the temperature is raised to 600-700°C, and the melt is impacted and melted by a high-pressure airflow of 1-3.5MPa, and the melt is broken into gas atomization particles, and after cooling, the zinc-magnesium alloy powder prepared by gas atomization technology is obtained; The obtained zinc-magnesium alloy powder is sieved to obtain a zinc-magnesium alloy powder with a particle size of 5-50 μm; Step 2) Bracket printing: The obtained zinc-magnesium alloy powder was used as a substrate for 3D printing using metal laser printing technology, and the obtained bracket was polished with sandpaper to remove unmelted powder and impurities; Then, ethanol and deionized water are used for ultrasonic cleaning for 10-15 minutes, and then dried to obtain the initial zinc-magnesium alloy stent; Step 3) Fluorinated coating: The initial zinc-magnesium alloy stent is immersed in a sodium fluoride solution with a mass percentage concentration of 8% to 23% to perform a fluorination reaction to form a fluorinated coating; After the fluorination reaction is completed, the surface of the stent is cleaned with deionized water to remove the residual fluoride liquid and impurities. Then, the stent is dried in a drying oven to ensure that the coating is dry and stable, and a zinc-magnesium alloy stent with a fluorinated coating can be obtained; Step 4) Fiber coating: Dissolve sodium alginate in distilled water at 30°C, stir, swell and dissolve to form a uniform and transparent sodium alginate solution; The homemade collagen was dissolved in a 0.5 mol / L acetic acid aqueous solution, stirred, swollen, and dissolved at room temperature to form a transparent and uniform collagen solution; Adding a pH regulator to adjust the pH value of the collagen solution to 6.50-6.70; 1-3 parts by volume of sodium alginate solution and 2-3 parts by volume of collagen solution are mixed and vigorously stirred to form a homogeneous system, and the blended spinning solution is filtered under a vacuum condition of 3-35 Pa to remove impurities and degas to a uniform solution; The prepared spinning solution is mixed with a water-based adhesive, and is sprayed evenly on the surface of the zinc-magnesium alloy bracket by a special fiber spraying device at a controlled pressure of 5-10Mpa. After natural drying, the target product can be obtained.

2. The method according to claim 1, characterized in that The zinc-magnesium alloy powder in step 1 has a metal zinc content of 84-93% by mass and a metal magnesium content of 7-16% by mass.

3. The method according to claim 1, characterized in that: In step 1, the high-pressure gas flow is nitrogen or argon.

4. The method according to claim 1, characterized in that: The fluorination reaction time is 1-1.5h.

5. The method according to claim 1, characterized in that In step 4, the percentage concentration of the sodium alginate solution is controlled at 8%-11%.

6. The method according to claim 1, characterized in that In step 4, the percentage concentration of the collagen solution is controlled at 9-13.5%.

7. A 3D printed stent prepared by the method according to any one of claims 1 to 6.

8. Use of the 3D printed scaffold according to claim 7 in the culture of bone marrow mesenchymal stem cells.

Citation Information

Cited By

  • Composite material mixed scaffold for bone repair and preparation method of composite material mixed scaffold

    CN120393115A